Thermal barrier coating with nano-composite double-layer ceramic structure and preparation method of thermal barrier coating

By using high-entropy alloy Fe22Cr28Al26B13W11 and rare earth modified zirconia and other materials, combined with supersonic flame spraying and plasma spraying technology, a nanocomposite double-layer ceramic structural thermal barrier coating was prepared, solving the complex preparation process of existing thermal barrier coating materials. , high cost and insufficient upper temperature resistance limit, achieving excellent high-temperature thermal shock resistance and low thermal conductivity.

CN119491184APending Publication Date: 2025-02-21SHIPBUILDING TECHNOLOGY RESEARCH INSITITUTE (NO 11 INSTITUTE OF CSSC)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411488686.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The preparation process of existing thermal barrier coating materials is complex and costly, and the upper temperature resistance limit is not enough to meet the maximum operating temperature requirements of the new marine low-speed engine fuel system.

Method used

The thermal barrier of nanocomposite double-layer ceramic structure is prepared by combining supersonic flame spraying and plasma spraying. coating.

Benefits of technology

The prepared thermal barrier coating has high temperature resistance, strong adhesion, low thermal conductivity, excellent thermal shock resistance, combined strengths are ≥20MPa, and the thermal conductivity reaches 0.90W/m·K, which is suitable for combustion of new ship low-speed engines. High temperature working environment in the room.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099392920000141
    Figure BDA0005099392920000141
Patent Text Reader

Abstract

The invention discloses a nano-composite double-layer ceramic structure thermal barrier coating and a preparation method thereof, and the nano-composite double-layer ceramic structure thermal barrier coating sequentially comprises a bonding layer, a middle layer and a surface layer from the surface of a low-carbon alloy steel substrate to the outside; the bonding layer is an alloy bonding layer formed by adopting high-entropy alloy Fe < 22 > Cr < 28 > Al < 26 > B < 13 > W < 11 > powder; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, the TiO2 accounts for 2%-4%, the SiO2 accounts for 1%-3%, and the balance is Al2O3; the surface layer is a ceramic layer formed by rare earth modified zirconium oxide and comprises the following raw material components in percentage by weight: 76%-83% of a mixture of ZrO2 and HfO2, 8%-11% of Y2O3, 5%-7% of Yb2O3 and 4%-6% of Gd2O3. The thermal barrier coating with the double-layer ceramic structure has ultrahigh-temperature environment resistance and relatively low thermal conductivity, and can effectively reduce the heat loss of a thermal component of a marine low-speed machine and improve the energy efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal spray coatings, and in particular to a nano-composite double-layer ceramic structure thermal barrier coating and a preparation method thereof. Background Art

[0002] As my country's new generation of marine engines transforms towards energy conservation, environmental protection and sustainability, the materials of key engine parts are also facing broader opportunities and new challenges. At this stage, advanced structural materials and advanced functional materials such as lightweight materials, thermal insulation materials, wear-resistant materials, corrosion-resistant materials, and damage-resistant materials are one of the main bottlenecks of my country's new low-carbon and zero-carbon marine engines. Taking thermal insulation materials as an example, from 1940 to the present, the average temperature in the engine combustion chamber has risen by 15°C each year, the pressure inside the combustion chamber has increased by 3 times, and the working conditions in the combustion chamber have become more and more harsh. Research and development of new thermal barrier coating materials with better performance can greatly improve the working environment of combustion chamber parts and reduce the loss of heat energy.

[0003] Thermal barrier coatings usually refer to thermal protective coatings deposited on the surface of gas turbine high-temperature alloys with good thermal insulation effects. Thermal barrier coatings are usually composed of a high-temperature oxidation-resistant alloy bonding layer and a ceramic layer with thermal insulation effects. They can reduce the operating temperature of the substrate and slow down high-temperature oxidation and corrosion, which is of great significance for ensuring the long-term service of the hot end components of the gas turbine. Among them, the bonding layer is an important component of the thermal barrier coating. When serving at high temperatures, a thin layer of thermally generated oxide that is not easily permeable to oxygen is formed on the surface of the bonding layer. When the thermal barrier coating fails, the ceramic layer often peels off from the interface near the oxide layer. The composition of the bonding layer is closely related to the growth of the oxide layer and the bonding state of the oxide layer with the ceramic and bonding layer, which greatly affects the service life of the thermal barrier coating.

[0004] At present, the mainstream thermal barrier coating material is still yttria-stabilized zirconia (YSZ), but with the development of engines, the operating temperature is getting higher and higher, and the microstructure of the YSZ coating will change significantly. In view of the problem of phase change at high temperature faced by YSZ coating, more and more researchers have conducted a lot of research on YSZ. At present, there are many studies on rare earth oxide R2O3 modified YSZ. R2O3 can not only reduce the thermal conductivity of YSZ coating, but also improve the sintering resistance of YSZ, which will greatly increase the number of high-temperature thermal shock resistance of the coating and extend the service life of the thermal barrier coating.

[0005] Patent document CN111809094A discloses a high-entropy alloy resistant to high-temperature oxidation, a thermal barrier coating and a preparation method of the thermal barrier coating; the molar content of each element in the AlCoCrFeNiTaHfY high-entropy alloy is: Al16-22%, Co14-20%, Cr14-20%, Fe5-8%, Ni38-45%, Ta1-2%, Hf0.02-0.1% and Y0.2-0.5%; the preparation method of the thermal barrier coating comprises: smelting in a vacuum arc furnace to obtain AlCoCrFeNiTaHfY high-entropy alloy powder; performing surface pretreatment on a high-temperature alloy substrate; depositing the AlCoCrFeNiTaHfY high-entropy alloy powder on the high-temperature alloy substrate by supersonic plasma spraying to prepare a bonding layer; and depositing a YSZ ceramic layer on the surface of the bonding layer by supersonic plasma spraying. However, this document adopts the vacuum arc furnace melting method to prepare high entropy alloys, because the required vacuum degree is high, and multiple melting processes are required to obtain high entropy alloy powder with uniform composition, which has high production costs; the thermal barrier coating ceramic layer only uses 6-8wt% Y2O3-stabilized ZrO2, and its upper temperature resistance limit is 1200°C, which can no longer meet the maximum operating temperature requirements of the new ship low-speed engine fuel system.

[0006] The present invention aims to provide a nanocomposite double-layer ceramic structure thermal barrier coating and its preparation method which is simple in method, easy to operate, and has good environmental performance, and is resistant to high temperature, has strong adhesion, low thermal conductivity, and excellent high-temperature thermal shock resistance, and meets the requirements for use in low-speed engine combustion chambers in the ship field in new fuel systems. Summary of the invention

[0007] The purpose of the present invention is to provide a nanocomposite double-layer ceramic structure thermal barrier coating and a preparation method thereof, so as to solve the problems of complex preparation process of high entropy alloy powder, high cost and low upper temperature resistance limit of thermal barrier coating in the prior art.

[0008] In order to achieve the above object, the technical solution of the present invention is:

[0009] The nanocomposite double-layer ceramic structure thermal barrier coating of the present invention comprises a bonding layer, an intermediate layer and a surface layer from the surface of the low-carbon alloy steel substrate outward in sequence; it is characterized in that:

[0010] The bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11The alloy bonding layer is formed by powder and has a thickness of 50 to 100 μm; the intermediate layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, wherein TiO2 accounts for 2% to 4% of the total mass of the intermediate layer, SiO2 accounts for 1% to 3% of the total mass of the intermediate layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the components of the rare earth modified zirconia are 76% to 83% of a mixture of ZrO2 and HfO2, 8% to 11% of Y2O3, 5% to 7% of Yb2O3 and 4% to 6% of Gd2O3; the mass ratio of the ZrO2 and HfO2 mixture is (90 to 95): (5 to 10).

[0011] Preferably, the material of the low-carbon alloy steel matrix is ​​one of 15CrMo, 35CrMo, and S20CrMoVS.

[0012] Preferably, the high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The powder is prepared by a mechanical alloying method using Fe powder, Cr powder, Al powder, B powder and W powder, wherein the atomic ratio of the Fe powder, Cr powder, Al powder, B powder and W powder is (20-26): (24-28): 26: (10-15): 11, and the particle size of the alloy powder is ≤48 μm; the high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The powder and the preparation method thereof adopt the alloy powder material for the bonding layer of the thermal barrier coating disclosed in the patent document CN118726862A and the preparation method thereof.

[0013] The method for preparing a nanocomposite double-layer ceramic structure thermal barrier coating according to the present invention comprises the following steps:

[0014] S1, degreasing and sand blowing the area to be sprayed and the adjacent area of ​​the low-carbon alloy steel substrate to blow away the floating dust on the surface of the parts;

[0015] S2, spraying the area to be sprayed of the low-carbon alloy steel substrate, depositing a bonding layer, an intermediate layer and a surface layer in sequence; spraying the bonding layer by a supersonic flame spraying process, and spraying the intermediate layer and the surface layer by an atmospheric plasma spraying process;

[0016] S3, subjecting the sprayed thermal barrier coating to a thermal diffusion treatment under vacuum; cooling the furnace as the temperature decreases, thereby obtaining the nanocomposite double-layer ceramic structure thermal barrier coating.

[0017] Preferably, the degreasing treatment in step S1 is to remove oil stains by soaking in acetone, then ultrasonically clean the substrate by using anhydrous ethanol as a medium, and finally dry the low-carbon alloy steel substrate.

[0018] Preferably, the supersonic flame spraying process parameters of step S2 are: spraying distance is 300-360 mm, powder feeding rate is 45-55 g / min, spraying angle is 75°-90°, oxygen flow rate is 1700-1750 SCFH, pressure is 180-200 psi, kerosene flow rate is 6.5-7.5 GPH, and pressure is 150-200 psi.

[0019] Preferably, the atmospheric plasma spraying process parameters of step S2 are: current of 550-600A, voltage of 60-75V, spraying distance of 90-110mm, spraying angle of 75°-90°; argon is used as the main gas, the gas pressure is 40-50slpm, hydrogen is used as the secondary gas, the gas pressure is 12-16slpm, the powder feeding rate is 25-40g / min, and the gun travel rate is 300-500mm / s.

[0020] Preferably, the vacuum degree of the thermal diffusion treatment in step S3 is (5-8)×10 -3 Pa, the temperature is 1050 ~ 1250 ℃, the time is 1.5 ~ 3.5h, and the temperature rises and falls with the furnace.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention adopts YSZ ceramic modified by Yb2O3 and Gd2O3 as the surface layer, aluminum oxide / titanium oxide ceramic as the middle layer, and high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 As an alloy bonding layer, a nano-composite double-layer ceramic structure thermal barrier coating with low thermal conductivity and excellent high-temperature thermal shock resistance is prepared by combining supersonic flame spraying with plasma spraying; the coating has uniform thickness, high temperature resistance, strong adhesion, low thermal conductivity, excellent high-temperature thermal shock resistance, etc. The coating bonding strength is ≥20MPa, the thermal conductivity reaches 0.90W / m·K, and the thermal expansion coefficient reaches 12.4ppm / K; the thermal barrier coating is not easy to fall off due to phase change in the high-temperature working environment of the low-speed engine combustion chamber, and can effectively prevent the heat loss of the low-speed engine combustion chamber, ensuring the thermal insulation and service life of the composite double-layer ceramic structure thermal barrier coating. The method of the present invention has a simple preparation process, is easy to operate, and has good environmental performance. DETAILED DESCRIPTION

[0023] Those skilled in the art should recognize that the present embodiment is only used to illustrate the present invention, and is not used to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.

[0024] Example 1

[0025] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel 15CrMo substrate to the outside, there are bonding layer, middle layer and surface layer in sequence; the bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The alloy bonding layer formed by powder has a thickness of 80μm; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, of which TiO2 accounts for 3% of the total mass of the middle layer, SiO2 accounts for 2% of the total mass of the middle layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the composition of rare earth modified zirconia is 80% of ZrO2 and HfO2 mixture (the mass ratio of the two is 95:5), 8% Y2O3, 6% Yb2O3 and 6% Gd2O3. The preparation process of the thermal barrier coating is as follows:

[0026] S1, pre-treat the substrate: soak the low-carbon alloy steel 15CrMo in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning and dry; then use white corundum as a sandblasting material to perform sandblasting on the area to be sprayed on the low-carbon alloy steel 15CrMo substrate, and use clean compressed air to blow away the floating dust on the surface of the parts. The surface roughness of the low-carbon alloy steel 15CrMo substrate is controlled at about 6.5μm.

[0027] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 For the alloy layer, the spraying distance is 330 mm, the powder feeding rate is 50 g / min, the spraying angle is 80 degrees, the oxygen flow rate (SCFH) is 1730, the pressure (psi) is 190, the kerosene flow rate (GPH) is 7.0, and the pressure (psi) is 180.

[0028] A ceramic intermediate layer of Al2O3+3%TiO2+2%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 550A, the voltage is 62V, the spraying distance is 100mm, and the spraying angle is 90°. During the spraying process, argon is used as the main gas, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 16slpm; the powder feeding gas is argon, the powder feeding rate is 25g / min, and the gun travel rate is 300mm / s.

[0029] Plasma spraying is used to deposit a ceramic surface layer of 80% (ZrO2+HfO2)+8% Y2O3+6% Yb2O3+6% Gd2O3 on the surface of the intermediate layer. The spraying current is 580A, the voltage is 65V, the spraying distance is 90mm, and the spraying angle is 90°. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 16slpm; the powder feeding gas is argon, the powder feeding rate is 35g / min, and the gun travel rate is 330mm / s.

[0030] S3, heat treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2 h, with a vacuum degree of 5×10 -3 Pa, the temperature is 1050℃, and the temperature rises and falls with the furnace.

[0031] Finally, the low-carbon alloy steel 15CrMo substrate is formed from the surface to the outside, which is: alloy Fe with a thickness of 80 μm 22 Cr 28 Al 26 B 13 W 11 A double-layer ceramic structure thermal barrier coating with a layer and a thickness of 310μm.

[0032] Example 2

[0033] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel 15CrMo substrate to the outside, there are bonding layer, middle layer and surface layer in sequence; the bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The alloy bonding layer formed by powder has a thickness of 70μm; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, of which TiO2 accounts for 2% of the total mass of the middle layer, SiO2 accounts for 3% of the total mass of the middle layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the composition of rare earth modified zirconia is 82% of ZrO2 and HfO2 mixture (the mass ratio of the two is 95:5), 9% Y2O3, 5% Yb2O3 and 4% Gd2O3. The preparation process of the thermal barrier coating is as follows:

[0034] S1, pre-treat the substrate: first, soak the low-carbon alloy steel 15CrMo in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning, and finally dry it; then use white corundum as a sandblasting material to perform sandblasting on the area to be sprayed on the low-carbon alloy steel 15CrMo substrate, and use clean compressed air to blow away the floating dust on the surface of the parts. The surface roughness of the low-carbon alloy steel 15CrMo substrate is controlled at about 6.5μm.

[0035] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 The alloy layer was sprayed at a distance of 300 mm, a powder feeding rate of 450 g / min, a spraying angle of 75 degrees, an oxygen flow rate (SCFH) of 1700, a pressure (psi) of 180, a kerosene flow rate (GPH) of 6.5, and a pressure (psi) of 150.

[0036] A ceramic intermediate layer of Al2O3+2%TiO2+3%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 560A, the voltage is 70V, the spraying distance is 95mm, and the spraying angle is 85 degrees. During the spraying process, argon is used as the main gas, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 14slpm; the powder feeding gas is argon, the powder feeding rate is 35g / min, and the gun travel rate is 350mm / s.

[0037] Plasma spraying is used to deposit a ceramic surface layer of 82% (ZrO2+HfO2)+9% Y2O3+5% Yb2O3+4% Gd2O3 on the surface of the intermediate layer. The spraying current is 580A, the voltage is 75V, the spraying distance is 110mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 15slpm; the powder feeding gas is argon, the powder feeding rate is 40g / min, and the gun travel rate is 400mm / s.

[0038] S3, thermal diffusion treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2 h, with a vacuum degree of 5×10 -3 Pa, the temperature is 1050℃, and the temperature rises and falls with the furnace.

[0039] Finally, the low-carbon alloy steel 15CrMo substrate is formed from the surface to the outside: alloy Fe with a thickness of 70 μm 22 Cr 28 Al 26B 13 W 11 A double-layer ceramic structure thermal barrier coating with a layer thickness of 280μm.

[0040] Example 3

[0041] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel 15CrMo substrate to the outside, there are bonding layer, middle layer and surface layer in sequence; the bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The alloy bonding layer formed by powder has a thickness of 100μm; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, of which TiO2 accounts for 4% of the total mass of the middle layer, SiO2 accounts for 1% of the total mass of the middle layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the composition of rare earth modified zirconia is 79% of ZrO2 and HfO2 mixture (the mass ratio of the two is 95:5), 11% Y2O3, 5% Yb2O3 and 5% Gd2O3. The preparation process of the thermal barrier coating is as follows:

[0042] S1, pre-treat the substrate: first, soak the low-carbon alloy steel 15CrMo in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning, and finally dry it; then use white corundum as a sandblasting material to perform sandblasting on the area to be sprayed on the low-carbon alloy steel 15CrMo substrate, and use clean compressed air to blow away the floating dust on the surface of the parts. The surface roughness of the low-carbon alloy steel 15CrMo substrate is controlled at about 6.5μm.

[0043] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 The alloy layer was sprayed at a distance of 300 mm, a powder feeding rate of 45 g / min, a spraying angle of 90 degrees, an oxygen flow rate (SCFH) of 1750, a pressure (psi) of 200, a kerosene flow rate (GPH) of 7.5, and a pressure (psi) of 200.

[0044] A ceramic intermediate layer of Al2O3+4%TiO2+1%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 600A, the voltage is 75V, the spraying distance is 110mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is slpm 45; hydrogen is used as the secondary gas, and the secondary gas pressure is slpm 16; the powder feeding gas is argon, the powder feeding rate is 45g / min, and the gun travel rate is 500mm / s.

[0045] A ceramic surface layer of 79% (ZrO2+HfO2)+11% Y2O3+5% Yb2O3+5% Gd2O3 is deposited on the surface of the intermediate layer by plasma spraying. The spraying current is 590A, the voltage is 73V, the spraying distance is 95mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 15slpm; the powder feeding gas is argon, the powder feeding rate is 40g / min, and the gun moving rate is 400mm / s.

[0046] S3, thermal diffusion treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2 h, with a vacuum degree of 5×10 -3 Pa, the temperature is 1050℃, and the temperature rises and falls with the furnace.

[0047] Finally, the low carbon alloy steel 15CrMo substrate is formed from the surface to the outside, which is: alloy Fe with a thickness of 100 μm 22 Cr 28 Al 26 B 13 W 11 A double-layer ceramic structure thermal barrier coating with a layer and a thickness of 300μm.

[0048] Example 4

[0049] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel S20CrMoVS substrate to the outside, there are bonding layer, middle layer and surface layer in sequence; the bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11The alloy bonding layer formed by powder has a thickness of 90μm; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, of which TiO2 accounts for 3% of the total mass of the middle layer, SiO2 accounts for 2% of the total mass of the middle layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the composition of rare earth modified zirconia is 80% of ZrO2 and HfO2 mixture (the mass ratio of the two is 90:10), 10% Y2O3, 4% Yb2O3 and 6% Gd2O3. The preparation process of the thermal barrier coating is as follows:

[0050] S1, pre-treat the substrate: first, soak the low-carbon alloy steel S20CrMoVS in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning, and finally dry it; then use white corundum as the sandblasting material to blow sand on the area to be sprayed on the low-carbon alloy steel S20CrMoVS substrate, and use clean compressed air to blow away the floating dust on the surface of the part. The surface roughness of the low-carbon alloy steel S20CrMoVS substrate is controlled at about 6.5μm.

[0051] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 The alloy layer was sprayed at a distance of 320 mm, a powder feeding rate of 46 g / min, a spraying angle of 90 degrees, an oxygen flow rate (SCFH) of 1730, a pressure (psi) of 190, a kerosene flow rate (GPH) of 7.0, and a pressure (psi) of 200.

[0052] A ceramic intermediate layer of Al2O3+3%TiO2+2%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 550A, the voltage is 70V, the spraying distance is 100mm, and the spraying angle is 80 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is slpm 45; hydrogen is used as the secondary gas, and the secondary gas pressure is slpm 15; the powder feeding gas is argon, the powder feeding rate is 40g / min, and the gun travel rate is 450mm / s.

[0053] Plasma spraying is used to deposit a ceramic surface layer of 80% (ZrO2+HfO2)+10% Y2O3+4% Yb2O3+6% Gd2O3 on the surface of the intermediate layer. The spraying current is 590A, the voltage is 73V, the spraying distance is 95mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 15slpm; the powder feeding gas is argon, the powder feeding rate is 35g / min, and the gun movement rate is 300mm / s.

[0054] S3, thermal diffusion treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2.5 h, with a vacuum degree of 7×10 -3 Pa, the temperature is 1150℃, and the temperature rises and falls with the furnace.

[0055] Finally, the low carbon alloy steel S20CrMoVS substrate surface is formed in the following order: alloy Fe with a thickness of 90 μm 22 Cr 28 Al 26 B 13 W 11 A double-layer ceramic structure thermal barrier coating with a layer and a thickness of 300μm.

[0056] Comparative Example 1

[0057] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel 15CrMo substrate to the outside, is a bonding layer, an intermediate layer, and a surface layer in order; the bonding layer is an alloy bonding layer formed by the existing technology NiCoCrAlY, with a thickness of 70μm; the intermediate layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, wherein TiO2 accounts for 2% of the total mass of the intermediate layer, SiO2 accounts for 3% of the total mass of the intermediate layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the components of the rare earth modified zirconia are 82% of a mixture of ZrO2 and HfO2, 9% of Y2O3, 5% of Yb2O3 and 4% of Gd2O3. The preparation process of the thermal barrier coating is as follows:

[0058] S1, pre-treat the substrate: first, soak the low-carbon alloy steel 15CrMo in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning, and finally dry it; then use white corundum as a sandblasting material to perform sandblasting on the area to be sprayed on the low-carbon alloy steel 15CrMo substrate, and use clean compressed air to blow away the floating dust on the surface of the parts. The surface roughness of the low-carbon alloy steel 15CrMo substrate is controlled at about 6.5μm.

[0059] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 The alloy layer was sprayed at a distance of 300 mm, a powder feeding rate of 450 g / min, a spraying angle of 75 degrees, an oxygen flow rate (SCFH) of 1700, a pressure (psi) of 180, a kerosene flow rate (GPH) of 6.5, and a pressure (psi) of 150.

[0060] A ceramic intermediate layer of Al2O3+2%TiO2+3%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 560A, the voltage is 70V, the spraying distance is 95mm, and the spraying angle is 85 degrees. During the spraying process, argon is used as the main gas, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 14slpm; the powder feeding gas is argon, the powder feeding rate is 35g / min, and the gun travel rate is 350mm / s.

[0061] Plasma spraying is used to deposit a ceramic surface layer of 82% (ZrO2+HfO2)+9% Y2O3+5% Yb2O3+4% Gd2O3 on the surface of the intermediate layer. The spraying current is 580A, the voltage is 75V, the spraying distance is 110mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 15slpm; the powder feeding gas is argon, the powder feeding rate is 40g / min, and the gun travel rate is 400mm / s.

[0062] S3, thermal diffusion treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2 h, with a vacuum degree of 5×10 -3 Pa, the temperature is 1050℃, and the temperature rises and falls with the furnace.

[0063] Finally, the low-carbon alloy steel 15CrMo substrate is formed from the surface to the outside: alloy Fe with a thickness of 70 μm 22 Cr 28 Al 26 B 13 W 11 A double-layer ceramic structure thermal barrier coating with a layer thickness of 280μm.

[0064] Comparative Example 2

[0065] A nanocomposite double-layer ceramic structure thermal barrier coating, from the surface of the low-carbon alloy steel S20CrMoVS substrate to the outside, there are bonding layer, middle layer and surface layer in sequence; the bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The alloy bonding layer formed by powder has a thickness of 90μm; the middle layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, of which TiO2 accounts for 3% of the total mass of the middle layer, SiO2 accounts for 2% of the total mass of the middle layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of ZrO2 stabilized by 8wt% Y2O3. The preparation process of the thermal barrier coating is as follows:

[0066] S1, pre-treat the substrate: first, soak the low-carbon alloy steel S20CrMoVS in acetone to remove oil stains, then use anhydrous ethanol for ultrasonic cleaning, and finally dry it; then use white corundum as the sandblasting material to blow sand on the area to be sprayed on the low-carbon alloy steel S20CrMoVS substrate, and use clean compressed air to blow away the floating dust on the surface of the part. The surface roughness of the low-carbon alloy steel S20CrMoVS substrate is controlled at about 6.5μm.

[0067] S2, spraying the area to be sprayed on the low-carbon alloy steel substrate to deposit the bonding layer: Fe 22 Cr 28 Al 26 B 13 W 11 The alloy layer was sprayed at a distance of 320 mm, a powder feeding rate of 46 g / min, a spraying angle of 90 degrees, an oxygen flow rate (SCFH) of 1730, a pressure (psi) of 190, a kerosene flow rate (GPH) of 7.0, and a pressure (psi) of 200.

[0068] A ceramic intermediate layer of Al2O3+3%TiO2+2%SiO2 is deposited on the surface of the bonding layer by plasma spraying. The spraying current is 550A, the voltage is 70V, the spraying distance is 100mm, and the spraying angle is 80 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is slpm 45; hydrogen is used as the secondary gas, and the secondary gas pressure is slpm 15; the powder feeding gas is argon, the powder feeding rate is 40g / min, and the gun travel rate is 450mm / s.

[0069] A 6wt% Y2O3-stabilized ZrO2 ceramic surface layer is deposited on the surface of the intermediate layer by plasma spraying. The spraying current is 590A, the voltage is 73V, the spraying distance is 95mm, and the spraying angle is 90 degrees. Argon is used as the main gas during the spraying process, and the main gas pressure is 45slpm; hydrogen is used as the secondary gas, and the secondary gas pressure is 15slpm; the powder feeding gas is argon, the powder feeding rate is 35g / min, and the gun travel rate is 300mm / s.

[0070] S3, thermal diffusion treatment: The sprayed thermal barrier coating was placed in a homemade heat treatment equipment for thermal diffusion treatment for 2 h, with a vacuum degree of 6×10 -3 Pa, the temperature is 1150℃, and the temperature rises and falls with the furnace.

[0071] Finally, the low carbon alloy steel S20CrMoVS substrate surface is formed in the following order: alloy Fe with a thickness of 90 μm 22 Cr 28 Al 26 B 13 W 11Layer, thermal barrier coating with a thickness of 300μm.

[0072] Test experiment example

[0073] The double-layer ceramic structure thermal barrier coatings of Examples 1 to 4 and Comparative Examples 1 to 2 were tested.

[0074] (1) The cross section of the thermal barrier coating sample was examined by metallographic method. The thickness of the thermal barrier coating was observed and measured at a magnification of 200 times. The total thickness of the thermal barrier coating (including the bonding transition layer of the thermal barrier coating) was measured to be approximately 300 μm. After multi-point measurement, the thickness was between 250 and 400 μm.

[0075] (2) After spraying thermal barrier coating on the Φ25×50 mm specimen, the specimen was bonded to a Φ25×50 mm loading block using adhesive according to the method specified in GB / T 8642-2002. The tensile test was performed on a universal testing machine. The results showed that the coating bonding strength was ≥40 MPa.

[0076] (3) The thermal diffusion coefficient λ(T) and specific heat capacity Cp(T) of the coating were tested using LFA427 / 7 / G, Netzsch laser thermal conductivity meter, and the thermal conductivity of the thermal barrier coating was calculated according to the method specified in standard GJB1201.1-1991.

[0077] (4) The thermal expansion coefficient of the thermal barrier coating is tested according to the method specified in standard GB / T 16535-2008.

[0078] (5) The thermal shock resistance of the thermal barrier coating after water cooling at 1300°C was tested according to the method specified in GB / T 16536-1996. After 200 cycles, the overall morphology of the thermal barrier coating before and after the test was observed.

[0079] Table 1 Performance test results of thermal barrier coatings of Examples 1 to 4 and Comparative Examples 1 to 2

[0080]

[0081] It can be seen from Table 1 that the bonding strength, thermal expansion coefficient and thermal shock resistance index of Examples 1 to 4 of the present invention are significantly improved compared with those of Comparative Examples 1 to 2, which proves that the present invention forms a denser thermal barrier coating, which improves the bonding strength of the coating. At the same time, the dense coating also effectively reduces the internal through-voids of the coating, thereby improving the high-temperature oxidation resistance of the coating.

Claims

1. A nanocomposite double-layer ceramic structure thermal barrier coating, which is composed of a bonding layer, an intermediate layer, and a surface layer from the surface of a low-carbon alloy steel substrate to the outside; characterized in that: The bonding layer is made of high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The alloy bonding layer is formed by powder and has a thickness of 50 to 100 μm; the intermediate layer is a ceramic layer composed of Al2O3, TiO2 and SiO2, wherein TiO2 accounts for 2% to 4% of the total mass of the intermediate layer, SiO2 accounts for 1% to 3% of the total mass of the intermediate layer, and the balance is Al2O3; the surface layer is a ceramic layer composed of rare earth modified zirconia, and the components of the rare earth modified zirconia are 76% to 83% of a mixture of ZrO2 and HfO2, 8% to 11% of Y2O3, 5% to 7% of Yb2O3 and 4% to 6% of Gd2O3; the mass ratio of the ZrO2 and HfO2 mixture is (90 to 95): (5 to 10).

2. The nanocomposite double-layer ceramic structure thermal barrier coating according to claim 1, characterized in that: The material of the low-carbon alloy steel matrix is ​​one of 15CrMo, 35CrMo and S20CrMoVS.

3. The nanocomposite double-layer ceramic structure thermal barrier coating according to claim 1, characterized in that: The high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The powder is prepared by a mechanical alloying method using Fe powder, Cr powder, Al powder, B powder and W powder, wherein the atomic ratio of the Fe powder, Cr powder, Al powder, B powder and W powder is (20-26): (24-28): 26: (10-15): 11, and the particle size of the alloy powder is ≤48 μm.

4. The nanocomposite double-layer ceramic structure thermal barrier coating according to claim 3, characterized in that: The high entropy alloy Fe 22 Cr 28 Al 26 B 13 W 11 The powder and the preparation method thereof adopt the alloy powder material for the bonding layer of the thermal barrier coating disclosed in the patent document CN118726862A and the preparation method thereof.

5. The method for preparing a nanocomposite double-layer ceramic structure thermal barrier coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, degreasing and sand blowing the area to be sprayed and the adjacent area of ​​the low-carbon alloy steel substrate to blow away the floating dust on the surface of the parts; S2, spraying the area to be sprayed of the low-carbon alloy steel substrate, depositing a bonding layer, an intermediate layer and a surface layer in sequence; spraying the bonding layer by a supersonic flame spraying process, and spraying the intermediate layer and the surface layer by an atmospheric plasma spraying process; S3, subjecting the sprayed thermal barrier coating to a thermal diffusion treatment under vacuum; cooling the furnace as the temperature decreases, thereby obtaining the nanocomposite double-layer ceramic structure thermal barrier coating.

6. The method for preparing the nanocomposite double-layer ceramic structure thermal barrier coating according to claim 5, characterized in that: The degreasing treatment in step S1 is to remove oil stains by immersion in acetone, then use anhydrous ethanol as a medium for ultrasonic cleaning, and finally dry the low-carbon alloy steel substrate.

7. The method for preparing the nanocomposite double-layer ceramic structure thermal barrier coating according to claim 5, characterized in that: The supersonic flame spraying process parameters of step S2 are: spraying distance of 300-360 mm, powder feeding rate of 45-55 g / min, spraying angle of 75°-90°, oxygen flow rate of 1700-1750 SCFH, pressure of 180-200 psi, kerosene flow rate of 6.5-7.5 GPH, and pressure of 150-200 psi.

8. The method for preparing the nanocomposite double-layer ceramic structure thermal barrier coating according to claim 5, characterized in that: The atmospheric plasma spraying process parameters of step S2 are: current of 550-600A, voltage of 60-75V, spraying distance of 90-110mm, spraying angle of 75°-90°; argon is used as the main gas, the gas pressure is 40-50 slpm, hydrogen is used as the secondary gas, the gas pressure is 12-16slpm, the powder feeding rate is 25-40g / min, and the gun travel rate is 300-500mm / s.

9. The method for preparing the nanocomposite double-layer ceramic structure thermal barrier coating according to claim 5, characterized in that: The vacuum degree of the thermal diffusion treatment in step S3 is (5-8)×10 -3 Pa, the temperature is 1050 ~ 1250 ℃, the time is 1.5 ~ 3.5h, and the temperature rises and falls with the furnace.

Citation Information

Patent Citations

  • High-entropy alloy resistant to high-temperature oxidation, thermal barrier coating and preparation method thereof

    CN111809094A

  • Alloy powder material for thermal barrier coating bonding layer and preparation method of alloy powder material

    CN118726862A